Identification and Characterization of BmNPV m6A Sites and Their Possible Roles During Viral Infection - Zhang, Xing; Zhang, Yaxin; Pan, Jun; Gong, Chengliang; Hu, Xiaolong (Frontiers in Immunology, 2022)
Bombyx mori nucleopolyhedrovirus (BmNPV) is one of the most serious pathogens and causes serious economic losses in sericulture. At present, there is no epigenetic modification of BmNPV transcripts, especially of m6A, and this modification mediates diverse cellular and viral functions. This study showed that m6A modifications are widespread in BmNPV transcripts in virally infected cells and the identified m6A peaks with a conserved RRACH sequence. m6A sites predominantly appear in the coding sequences (CDS) and the 3′-end of CDS. About 37% of viral genes with m6A sites deleted from the viral genome did not produce any infectious virions in KOV-transfected cells. Among the viral genes related to replication and proliferation, ie-1 mRNA was identified with a higher m6A level than other viral genes. The m6A sites in the ie-1 mRNA may be negatively related to the protein expression. Viral replication was markedly inhibited in cells overexpressed with BmYTHDF3 in a dose-dependent manner, and a contrary effect was found in si-BmYTHDF3-transfected cells. Collectively, the identification of putative m6A modification in BmNPV transcripts provides a foundation for comprehensively understanding the viral infection, replication, and pathobiology in silkworms.